Clinical and genetic characteristics of the early 66th type epileptic encephalopathy (literature review and own observation) - T. V. Markova; A. O. Borovikov; E. R. Lozier; A. A. Isaev; V. S. Kaimonov; E. A. Pomerantseva; F. A. Konovalov; O. A. Schagina; E. L. Dadali (Нервно-мышечные болезни, 2020)
Early epileptic encephalopathy-66 was first diagnosed in a male patient from Russia using whole-exome sequencing. Early epileptic encephalopathy- 66 is a unique disorder in the group of early epileptic encephalopathies. The same recurrent heterozygous variant of the nucleotide sequence was found in all known patients, but the severity of seizures and dysmorphic signs significantly vary between patients. The current study of a recurrent pathogenic variant in PACS2 gene expands the phenotype spectrum of early epileptic encephalopathy-66 and will improve the management of patients with that disorder in Russia in the future.